The Set3/Hos2 histone deacetylase complex attenuates cAMP/PKA signaling to regulate morphogenesis and virulence of Candida albicans. - Denes Hnisz (Public Library of Science (PLoS), 2010)
Candida albicans, like other pleiomorphic fungal pathogens, is able to undergo a reversible transition between single yeast-like cells and multicellular filaments. This morphogenetic process has long been considered as a key fungal virulence factor. Here, we identify the evolutionarily conserved Set3/Hos2 histone deacetylase complex (Set3C) as a crucial repressor of the yeast-to-filament transition. Cells lacking core components of the Set3C are able to maintain all developmental phases, but are hypersusceptible to filamentation-inducing signals, because of a hyperactive cAMP/Protein Kinase A signaling pathway. Strikingly, Set3C-mediated control of filamentation is required for virulence in vivo, since set3Delta/Delta cells display strongly attenuated virulence in a mouse model of systemic infection. Importantly, the inhibition of histone deacetylase activity by trichostatin A exclusively phenocopies the absence of a functional Set3C, but not of any other histone deacetylase gene. Hence, our work supports a paradigm for manipulating morphogenesis in C. albicans through alternative antifungal therapeutic strategies.